Lethal letters - Adams, Ellery (Adams, Ellery. Books by the bay mystery., 2014)
When an item from a time capsule discovered in the foundation of a local church goes missing and a young woman is murdered, aspiring novelist Olivia Limoges investigates with the help of her fellow writers.